Funny little woman (The) - Mosel, Arlene (New York : Puffin Books, 1972)
In this tale set in Old Japan, a lively little woman who loves to laugh pursues her runaway dumpling and must outwit the wicked three-eyed oni when she lands in their clutches.
The Funny Little Woman is based on a tale by Lafacadio Hearn
Keywords: Folk Tales-Fiction